ᓯᕗᒧᐊᕐᕕᒃ Sivumuarvik, a place where one moves forward: a framework for design empathy in Nunavut - Duale, Mona (2024)
Country food is central to Inuit identity, communities, and the local economy in Nunavut (QIA, 2019). Spaces that facilitate the acquisition, processing, sharing, education, and storage of this food are essential for strengthening Inuit identity, building resilient communities, supporting food security, and adapting architecture from a southern model to one suited to northern and Inuit contexts. The previously nomadic Inuit way of life deeply connected food and place, with housing built from elements of the land (snow) or harvested animals (caribou skins). However, this intrinsic connection between place and identity is often lacking in the current built environment. This practicum explores Inuit cultural values that shape and reinforce identity, as expressed through their material culture. It considers placemaking and a sense of place as key methods for revitalizing the built environment’s relationship with people and the land. Ultimately, proposing a design approach rooted in Inuit societal values, employing a hybrid methodology that integrates Aajiiqatigiingniq, an Inuit research framework and empathy design into the architectural and design processes. The result is a new typology for community food-related infrastructure in Nunavut, in the design proposal of ᓯᕗᒧᐊᕐᕕᒃ Sivumuarvik, A Place Where One Moves Forward. February 2025